(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective: Diabetic foot syndrome is the most dramatic complication of diabetes mellitus. The treatment success is impossible without improving blood circulation and the elimination of hemodynamic disorders in the affected limb.The study aim was to evaluate mini-invasive revascularization operations effectiveness on the lower limbs peripheral arteries in neuro-ischemic and ischemic diabetic foot syndrome forms. Materials and methods: The study enrolled 104 patients with purulent-necrotic complications of diabetic foot syndrome. 54 (51.9%) patients underwent stenting and balloon angioplasty (the main group). The comparison group included 50 (48.1%) patients, undergoing indirect revascularization surgeries in complex treatment. Results and discussion:After endovascular interventions, the API index increased by 47.6% (p<0.01) after 20 days compared to the admission index, the average blood flow rate increased by 1.8 times (p<0.01), and the tPo2 value improved by 67.8% (p<0.01). In the control group, the tPo2 value increased by 40.3% after 20 days, and API – by 34.4%. In the main group, the swelling disappearance in the foot wounds area was by 3.7±0.5 days faster (p<0.001), wounds purification by 4.1 days (p<0.001), granulation appearance by 3.5±0.4 days (p<0.001), wound margins infiltration disappearance happened 3.3±0.9 days earlier (p<0.001), and the wound epithelization was 2.9 days earlier (p<0.01) than in the control group patients. Conclusion: Foot support function at discharge from hospital was preserved in 94.4% of the main group and in 84% of the control group. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.817-825